(untitled) (Academia Science Repository, 2023)
In this article is devoted to the using communicative approach in language teaching for the young learners and so that the effectiveness of the communicative approach techniques for the young learners in teaching and learning process. The main purpose of learning a foreign language is to enable our young learners to communicate in it. This is the process of arriving at the point of understanding a language, and this is where the communicative approach to language teaching and learning comes to the forefront. In recent years the communicative approach has become ever more popular and overall effective ways to facilitate second language learning.